2013
DOI: 10.4314/ejesm.v6i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Perceptions of Village Residents on the Health Risks Posed by Kadhodeki Dumpsite in Nairobi, Kenya.

Abstract: This study sought to assess the knowledge, attitude and perceptions of the residents of Kadhodeki village on the health risks posed by the Kadhodeki dumpsite. Using households as units of sampling, a descriptive cross sectional survey was carried out in June 2012. Random data were collected using a face-to-face researcher administered structured questionnaire and 323 participants were interviewed. Chi square was used to determine the association between the different variables. Findings indicate that residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…FHE has a positive impact (0.05) on PAPL2 , as hypothesized in the Conceptual model. This result is in line with [ 38 , 74 ]. As expected, and in line with [ 1 , 85 ], living in severely and moderately polluted areas increases both PAPL1 (MAP (0.09) and SAP (0.19)) and PAPL2 (MAP (0.06) and SAP (0.06)), although the latter impact is marginally significant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…FHE has a positive impact (0.05) on PAPL2 , as hypothesized in the Conceptual model. This result is in line with [ 38 , 74 ]. As expected, and in line with [ 1 , 85 ], living in severely and moderately polluted areas increases both PAPL1 (MAP (0.09) and SAP (0.19)) and PAPL2 (MAP (0.06) and SAP (0.06)), although the latter impact is marginally significant.…”
Section: Resultssupporting
confidence: 91%
“…A positive impact of FS on PAP is assumed, because in larger families more people are exposed than in smaller families. This assumption is supported by [ 72 , 74 ]. No direct impact of FS on EK is assumed.…”
Section: Conceptual Modelmentioning
confidence: 63%
“…The detailed reaction mechanism between nanoceria and H2O2 is quite complex, since H2O2 can act as an oxidizing agent, a reducing agent and a ligand [23]. This color change and the related redox reactions have been applied to design various sensors [9,22,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we also found that the willingness to pay for clean coal was positively affected by family size. In larger families, more people were exposed than in smaller families, so respondents with larger family sizes had higher risk perceptions and higher willingness to protect themselves [ 37 , 38 ]. The number of children in a family was positively correlated with self-protection willingness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%